2016
DOI: 10.1103/physrevc.93.064907
|View full text |Cite
|
Sign up to set email alerts
|

Vorticity in heavy-ion collisions

Abstract: We study the event-by-event generation of flow vorticity in the BNL Relativistic HeavyIon Collider Au + Au collisions and CERN Large Hadron Collider Pb + Pb collisions by using the HIJING model. Different definitions of the vorticity field and velocity field are considered. A variety of properties of the vorticity are explored, including the impact parameter dependence, the collision energy dependence, the spatial distribution, the event-by-event fluctuation of the magnitude and azimuthal direction, and the ti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
168
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 216 publications
(181 citation statements)
references
References 121 publications
(190 reference statements)
12
168
0
1
Order By: Relevance
“…[11] is inversely proportional to the collision energy. On the other hand, simulating results by a multi-phase transport (AMPT) model has shown that the averaged classical vorticity decreases with the collision energy [36,37], which, of course, leads to the decline of global polarization. It is also interesting to take a glance on the time evolution of polarization, shown in Fig.…”
mentioning
confidence: 99%
“…[11] is inversely proportional to the collision energy. On the other hand, simulating results by a multi-phase transport (AMPT) model has shown that the averaged classical vorticity decreases with the collision energy [36,37], which, of course, leads to the decline of global polarization. It is also interesting to take a glance on the time evolution of polarization, shown in Fig.…”
mentioning
confidence: 99%
“…More results can be found in Ref. [7]. Our study may be useful to the numerical simulation of the CVE, the CVW, and the Λ baryon spin polarization.…”
Section: Discussionmentioning
confidence: 94%
“…Recently, it was realized that noncentral heavy-ion collisions can also generate finite flow voriticty and thus provide us with a chance to study quark-gluon matter under local rotation [4,5,6,7]. The mechanism of the generation of finite vorticity is simple.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations